DAMPAK DARI PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MEREK M231 DI PT. RAMAYANA LESTARI SENTOSA, TBK PEMATANGSIANTAR - Ernest Grace; Desi Susanti; Eliza Arshandy; Vivi Candra; Rosita Manawari Girsang (Bajang Institute, 2024)
A good marketing concept is when it is able to make promotion a component that supports consumer purchasing decisions from the results of the business being run. The purpose of the study was conducted to determine the effect of promotion on purchasing decisions for the fashion brand M231. The results showed that the promotion variable had valid criteria and also the purchase decision also had valid criteria. The reliability test shows that promotions and purchasing decisions have reliable criteria. Then the results of the coefficient of determination show that the ability of promotion to explain purchasing decisions is 41%, and has a strong correlation. While the rest is not the main variable discussed in this study. The results of the simple regression equation Y = 30.980 + 0.478X, this shows that promotion has a positive direction coefficient on purchasing decisions, while for the partial hypothesis test it shows that there is a positive and significant effect of promotion on purchasing decisions